Enablers and barriers for hearing parents with deaf children: Experiences of parents and workers in Wales, UK - Julia Terry (Health Expectations, 2023)
More than 90% of deaf children are born to hearing families who know little about deafness. Benefits from hearing screening at birth are often lost, as families find little information about pathways for deaf children but are key to ensuring deaf children receive relevant language and communication support. Systems surrounding deaf children and family members are crucial for children's health and social development. Experiences of hearing parents raising deaf children and understanding factors that influence families' experience of navigating pathways for deaf children through health and education services are currently underreported.